Flavokawain B induced cytotoxicity in two breast cancer cell lines, MCF-7 and MDA-MB231 and inhibited the metastatic potential of MDA-MB231 via the regulation of several tyrosine kinases in vitro - Abu, Nadiah; Akhtar, Muhammad Nadeem; Yeap, Swee Keong; Lim, Kian Lam; Ho, Wan Yong; Abdullah, Mohd Puad; Ho, Chai Ling; Omar, Abdul Rahman; Ismail, Jamil; Mohammed Alitheen, Noorjahan Banu (BioMed Central, 2016)
Background: The kava-kava plant (Piper methysticum) is traditionally consumed by the pacific islanders and has been linked to be involved in several biological activities. Flavokawain B is a unique chalcone, which can be found in the roots of the kava-kava plant. In this study, the operational mechanism of the anti-cancer activity of a synthetic Flavokawain B (FKB) on two breast cancer cell lines, MCF-7 and MDA-MB231 was investigated. Method: Several in vitro assays were attempted such as MTT, flow cytometry of cell cycle analysis, annexin V analysis, and JC-1 analysis to detect apoptosis. Moreover, in vitro metastasis assays were also performed such as transwell migration assay, invasion assay, rat aorta ring and HUVEC tube formation. Molecular analysis of related genes and proteins were conducted using real-time PCR and proteome profiler analysis. Results: Based on our results, apoptosis was induced when both MCF-7 and MDA-MB231 were treated with FKB. A significant G2/M arrest was seen in MDA-MB231 cells. Additionally, FKB also inhibited the in vitro migration and invasion in MDA-MB231 cells in a dose dependent manner. Moreover, FKB can be a potential inhibitor in angiogenesis as it suppressed the formation of vessels in HUVEC cells as well as in the ex-vivo rat aortic ring assay. Conclusion: Our findings suggested that FKB also regulated several receptor tyrosine kinases. Overall, FKB is not only a potential candidate to be an anti-cancer agent, but as an anti-metastatic agent as well.